The impact of nurses' sense of security on turnover intention during the normalization of COVID-19 epidemic: The mediating role of work engagement - Tang, Yao; Dias Martins, Luís M.; Wang, Shi-bin; He, Qing-xia; Huang, Hui-gen (Frontiers in Public Health, 2022)
Background: COVID-19 pandemic has entered a phase of normal management in China. During this phase, nurses have an increased workload and mental health issues threatening their sense of security. Fewer studies have been conducted on nurses' sense of security and turnover intentions in this phase. This study aimed to investigate the interrelationship between nurses' sense of security, work engagement, and turnover intentions during the normalization phase of the epidemic in China and to explore the impact of sense of security on turnover intention. Methods: A cross-sectional survey was conducted from September 2020 to May 2021 in Guangdong Province, China. Data were collected online using Sense of Security Scale for Medical Staff (SSS-MS), Utrecht Work Engagement Scale(UWES), and Turnover Intention Scale. Pearson's correlation analysis was used to assess the correlation between sense of security, work engagement, and turnover intention. The hypothesis model used multiple linear regression models and the bootstrapping procedure to analyze the relationship between these variables. Results: Data were collected from 2,480 nurses who met the inclusion criteria. 64.5% of nurses had a high turnover intention or very high turnover intention. Sense of security was positively correlated with work engagement and negatively related to turnover intention. Work engagement was negatively correlated with turnover intention. After controlling the demographic and working variables, the sense of security had a direct positive effect on work engagement (β=0.291, P<0.001). Work engagement had a direct negative effect on turnover intention (β=-0.484, P<0.001). Sense of security had significant direct effect on turnover intention(β=--0.447, p<0.001). Work engagement mediated the negative association between sense of security and turnover intention. Work engagement partly mediates the relationship between all components of sense of security and turnover intention. Conclusions: Nurses' turnover intention was at a high level during the normalization phase of the epidemic. Sense of security and its components act as positive resources to reduce turnover intention by improving work engagement. Policy makers and managers may pay attention to the needs of nurses' sense of security, which may be a new perspective to help managers reduce their turnover intention and stabilize the nurse team.